POEMS Syndrome: The Important Role of Imaging in the Diagnosis - Grilo,Francisco (2023)
Abstract POEMS syndrome is a rare paraneoplastic syndrome associated with an underlying plasma cell disorder. Despite it being predominantly a clinical and laboratorial diagnosis, imaging can play a key role by identifying many of the diagnostic criteria. This case emphasizes the contribution of imaging to the diagnosis of this entity. A 67-year-old woman presents with a supraclavicular lymph node, asthenia and paresthesia and numbness of the lower extremities. Computed tomography (CT) revealed diffuse lymphadenopathy with characteristics suggestive of multicentric Castleman Disease, associated with sclerotic bone lesions, intraperitoneal fluid and hepatosplenomegaly. These findings combined with the presence of monoclonal plasma cell disorder and mild polyneuropathy allowed the correct diagnosis of POEMS syndrome to be established.